2007
DOI: 10.1287/orsc.1070.0292
|View full text |Cite
|
Sign up to set email alerts
|

Combining Patent Law Expertise with R&D for Patenting Performance

Abstract: Drawing on the resource-based view (RBV), this paper examines how the combination or bundling of resources influences firm-patenting performance. We hypothesize that firm-patenting output depends not only on research and development (R&D) resources, but also on the patent law expertise combined with R&D inside the firm. We predict that the specialization of this in-house legal resource to R&D enables firms to identify patentable inventions more effectively and to convert them into patents. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
100
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(110 citation statements)
references
References 54 publications
3
100
0
1
Order By: Relevance
“…In line with the literature (see e.g. Hall and Ziedonis, 2001;Somaya et al, 2007), the remaining overdispersion, as reported the Lagrange…”
supporting
confidence: 91%
See 2 more Smart Citations
“…In line with the literature (see e.g. Hall and Ziedonis, 2001;Somaya et al, 2007), the remaining overdispersion, as reported the Lagrange…”
supporting
confidence: 91%
“…Ahuja and Katila, 2001, Hall and Ziedonis, 2001, Somaya et al, 2007. Size is measured by the book value of the firms' tangible assets (ASSETS).…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the relationship between R&D capability and patentability are very wide in their range, have been deeply conducted and appeared to generally have positive effects (Artz et al, 2010;Hall and Bagchi-Sen, 2002;Hall and Ziedonis, 2001;Lin et al, 2006;Reitzig and Puranam, 2009;Romijn and Albaladejo, 2002;Somaya et al, 2007;Souitaris, 2002). Romijn and Albaladejo (2002), in their study on 33 of small enterprises related to electronics and software in southeastern district of England, proved that the capabilities of R&D has a correlation with the performance.…”
Section: Randd Capability and Performancementioning
confidence: 99%
“…Ahuja and Katila, 2001; Hall and Ziedonis, 2001; Somaya et al, 2007). Size is measured by the book value of the firms' tangible assets (assets).…”
Section: Control Variablesmentioning
confidence: 99%